Description of risk factors associated with the detection of BVDV antibodies in Brazilian pig herds - Gatto, Igor Renan Honorato [UNESP]; Linhares, Daniel Correia Lima; de Souza Almeida, Henrique Meiroz [UNESP]; Mathias, Luis Antônio [UNESP]; de Medeiros, Andrea Souza Ramos [UNESP]; Poljak, Zvonimir; Samara, Samir Issa [UNESP]; de Oliveira, Luis Guilherme [UNESP] (Springer Nature, 2018)
Bovine viral diarrhea virus (BVDV) infects ruminants as primary hosts. However, other animals like pigs are susceptible. This study was conducted to investigate seroprevalence and risk factors associated with the detection of BVDV antibodies in pig herds. A total of 1.705 serum samples of 33 finisher herds, from seven Brazilian states, were collected in slaughterhouses. The samples were tested by virus neutralization (VN) test. In total, 5.35% (91/1.705) were positive and 64% (21/33) of the herds had positive animals. A significant association with “trucks are not cleaned and disinfected” and “visitors do not respect 72-h interval between visits to farms” (P < 0.05) was found in association with detection of BVDV-2 antibodies. This study suggests that important biosecurity gaps are present in Brazilian pig farms, as the presence of BVDV antibodies in pigs suggests (direct or indirect) contact with population(s) of ruminant species. Closing biosecurity gaps prevents spread of BVDV and other pathogens such as foot-and-mouth disease virus (FMDV) between pig and ruminant farms. This data should be taken in account by CSF surveillance programs, once cross-reaction in serologic tests between classical swine fever virus (CSFV) and BVDV antibodies has been shown to occur.
Keywords: Interspecies infection; Pestivirus infection; Risk factors; Swine